PRIVATISASI BUMN DALAM PERSPEKTIF EKONOMIKELEMBAGAAN - Setyawan, Anton Agus (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
Indonesias government has been encouraging privatization programfor their corporation (BUMN). This program exists due to two mainreasons. First, privatization could be a way to solve the fiscal deficitproblem. Second, it proves to be one of the logical way to increaseBUMNs performance. This articles tries to analyze privatization byusing institutional economics approach. Institutional means aconvention or an appropriate manner in humans behavior whichresults a predictability in human inter-relationship. The tools ofanalyses of institutional economics is The Hierarchy of Public PolicyModel. This model could analyze the steps of public policy decisionsin privatization paradigm, wether pro-privatization or contra-privatization. This article also shows a few empirical results ofprivatization and how to buid an encouraging condition to improvethe result of this program